Materials for the Sumerian Lexicon XII. The Series lú = ša and Related Texts - Landsberger, Benno (1969)
Edited by M. Civil with the collaboration of R. D. Biggs, H. G. Güterbock, H. J. Nissen, E. Reiner. (A Reconstruction of Sumerian and Akkadian Lexical Texts prepared by B. Landsberger. Edited by E. Reiner and M. Civil.); L.it. 8.400/$14.00.